Role of nozzles with air holes in air entrainment by a water jet - Emiroglu, ME; Baylar, A (Canadian Assoc Water Quality, 2003)
When a water jet impinges a pool of water at rest, air bubbles may be entrained and carried a distance below the pool's surface. This process is called plunging water jet entrainment and aeration. This paper describes an experimental study of the air entrainment rate of circular nozzles with and without air holes, and in particular, the effect of varying numbers and positions of air holes and distance between the location of the air holes and nozzle exit. A negative pressure occurred due to the air holes on the circular nozzles. This phenomenon affected air entrainment. The differences in air entrainment rate were related to changes in the jet shape. It was demonstrated that the air entrainment rates of the circular nozzles with air holes were significantly higher than those of circular nozzles without air holes.
Keywords: aeration; air entrainment; air hole; nozzle; water jet